(untitled) (Texas Journal of Multidisciplinary Studies, 2025)
Insurance plays a critical role in protecting small businesses from a variety of financial risks that can threaten their operations and sustainability. Unlike large corporations, small businesses often lack the resources to recover from unexpected events such as property damage, lawsuits, or employee injuries. Therefore, obtaining the right types of insurance coverage is essential for mitigating potential losses and ensuring business continuity. This paper explores the most essential types of insurance policies that small businesses should consider, including general liability insurance, property insurance, workers’ compensation, professional liability insurance, and business interruption insurance. Each type addresses specific risks that could disrupt operations or cause severe financial hardship. The study also discusses emerging trends such as cyber liability insurance, which is increasingly relevant in the digital age.